Execution Speed up of Image Rotation Matrix Using Parallel Technique - Aldulaimi, Dr. Fahraldeen; Alshakargy, Hadeel (American Scientific Research Journal for Engineering, Technology, and Sciences, 2016)
In computer graphic science rotating a vertex in an image around a specific point in any direction is a time consuming mission. The rotation of a vertex depends on multiplying it’s coordinates by graphic geometric transformation matrices, this multiplication requires a considerable time. In this paper the acceleration of image rotation is achieved by using parallel techniques such as using Multicore Core Central Processing Unit (CPU) or General Purpose Graphic Processing Unit (GPGPU) or even both. The results show a significant increase in computation speed when rotating a large number of vertices by using CPU. A considerable acceleration is achieved when GPU is used to make image rotation. However the speedup is limited by the number of processing units available for parallel processing.